Diseño de una red de seguridad perimetral basada en OPEN SOURCE para aplicación de IDS E IPS para el control de amenazas informáticas en la Universidad Técnica de Babahoyo. - Cabrera Vásquez, Fani Yudid (2022)
Through this research, it is intended to present the design of a Perimeter Security Network based on Open Source for the application of IDS and IPS for the control of computer threats at the Technical University of Babahoyo, which allows proposing an implementation proposal to avoid internal attacks. and external that the institution may have, in a way that guarantees the confidentiality, integrity and availability of the data; therefore, the information is efficiently analyzed so that although the providers of internet companies have a high rate of vulnerabilities in relation to the network infrastructure, especially in the equipment of the central network, they must avoid any type of attack that comes from the internet or from its own internal network, guaranteeing the confidentiality, integrity and availability of the services. The objective of the research is to improve network security at UTB by evaluating the current situation of the institution with its respective functional requirements. For the collection of information, it was necessary to use the research technique of interviewing Engineers; in turn, this document gives way to obtaining information that is necessary to mitigate computer threats in the institution. This investigative compendium discloses reliable information that has been obtained through the use of tools, in order to know the current situation of the network, and at this point is where the vulnerabilities and their possible consequences that affect the network are identified. net.